STRATEGI PROGRAM GOOD MORNING HARD ROCKERS SHOW UNTUK MENINGKATKAN JUMLAH PENDENGAR - Sartika, Sartika; Wahyuni, Jauhar (The Commercium, 2023)
The radio program strategy, apart from increasing the number of listeners, is also very important to deal with current technological developments, especially with the post-pandemic conditions which have had an especially impact on advertising revenue. This research is a qualitative research with a case study method that aims to find out how the strategy applied to the Good Morning Hard Rockers Show program is to increase the number of listeners on Hard Rock FM Surabaya radio. The strategies studied were reviewed using program strategies by Susan Tyler Eastman (2012) which are divided into five strategic groups, namely compatibility strategies, habit formation, control of audience, conservation of program resources, and breadth of appeal. The results of this study indicate that the Good Morning Hard Rockers Show Program applies various strategies to increase the number of listeners which are divided into content and context strategies. Some of these strategies have steps that are in accordance with the five groups of program strategies by Susan Tyler Eastman (2012). From the research findings it was also found that the strategy implemented by the Good Morning Hard Rockers Show program could increase the number of listeners, both listeners to the program itself and other programs.